VD_FINDINFO Jug / 2013 / 230 vom 29. Mai 2013 - VD Tribunal cantonal (2013)
PORNOGRAPHIE, LOI FÉDÉRALE SUR LES STUPÉFIANTS ET LES SUBSTANCES PSYCHOTROPES | 106 CP, 19 al. 2 CP, 197 ch. 3 CP, 34 CP, 42 CP, 44 CP, 47 CP, 50 CP, 63 CP, 69 CP, 19a ch. 1 LStup